ANALISIS PENGARUH POLUSI CAHAYA TERHADAP PENENTUAN AWAL WAKTU SUBUH DI KABUPATEN BULUKUMBA BERDASARKAN DATA SKY QUALITY METER (SQM) - Putri, Amelia; Mustafa, Adriana (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract This study aims to analyze the impact of light pollution on determining the start of the *Subuh* (dawn) prayer time in Bulukumba Regency using a Sky Quality Meter (SQM). The research focuses on light pollution levels based on SQM measurements and their influence on the accuracy of determining the onset of *Subuh*. A qualitative method employing a field research approach was used. Primary data were obtained through direct measurements using an SQM, while secondary data were derived from books, journals, and various supporting references. Observation and documentation techniques were utilized to supplement the research data. The results indicate that: (1) observations using the Sky Quality Meter (SQM) at Panrangluhu Beach, Bulukumba Regency, reveal good sky quality with low levels of light pollution. The consistently recorded shift in sky magnitude values transitioning from darkness to brightness as sunrise approaches reflects the natural emergence of *fajr ṣādiq* (true dawn), thereby supporting a more objective determination of the *Subuh* start time; and (2) an analysis of the SQM value fluctuation graph from March 14–16, 2026, shows a distinct inflection point coinciding with the onset of dawn. Sky conditions with minimal light pollution allow for the detection of the *Subuh* start time based on astronomical parameters such as changes in sky brightness and the Sun's position or altitude angle with a higher degree of accuracy. Keywords: Light Pollution, Dawn Time, Sky Quality Meter, Astronomy, Fajar Ṣhadiq